MODERNIZATION OF ISLAMIC BOARDING SCHOOL: ADAPTATION OF TRADITIONAL VALUES IN CONTEMPORARY ISLAMIC EDUCATION - Rofiqotul Afifah Firdausiyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to describe the dynamics of modernization within Islamic boarding schools (pesantren), the strategies adopted to preserve traditional values in the modern era, and the challenges as well as implications of these changes for their Islamic identity. The research employs a descriptive qualitative approach through literature review and document analysis. The findings indicate that the modernization of pesantren occurs dynamically through transformations in systems, curricula, and educational orientations while maintaining core Islamic values. In responding to modern developments, pesantren have adopted integrative strategies such as combining religious and general education, implementing digital technology, and improving management practices based on transparency and efficiency. However, modernization also presents challenges, particularly concerns about the erosion of simplicity and spirituality that characterize pesantren life. Nevertheless, pesantren have demonstrated their ability to adapt selectively, preserving their Islamic identity and scholarly tradition amid ongoing social change.